DETERMINAN KESENJANGAN ANGGARAN DI KABUPATEN KEPULAUAN SULA - Muhaidin Masuku Muhaidin Masuku (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2022)
Abstract This study has several objectives including: (1) Analyzing and knowing how Budget Participation affects Budget Gap. (2) Analyze and find out how Information Asymmetry can moderate the relationship between Budget Participation and Budget Gap. (3) Analyze and find out how Ethics can moderate the relationship between Budget Participation and Budget Gap. This research uses quantitative methods. There are several research subjects including: the head of the department, the head of the planning subdivision, the head of the field and the head of the section in each regional government organization (OPD) of the Sula Islands. A total of 248 respondents were involved in this study, with sampling using positive sampling. This research has the following results: (1) Positive and significant influence on budget participation on budget gaps. (2) Information asymmetry and ethics are not moderating variables.